Território feito à mão: artesanato e identidade territorial no Rio Grande do Sul - Mello, Carolina Iuva de (2016)
Studies on culture and identity have reached significant relevance in the social sciences, with emphasis on the notion of territorial identity, present today as a mobilizing for the creation of new territoriality and promotion of territorial development strategies. Within these strategies, cultural goods, such as crafts, stand out among possible singularities linked to the territory that can be mobilized in the name of development. Thus, with reference to the experiences of the territories of Costa Doce and Quarta Colônia, in Rio Grande do Sul, the objective is to understand how the craft has been transformed in interaction with contemporary globalizing processes that nurture its drive while territorial identity expression. Specifically, the objective is (a) to demonstrate the growing rapprochement between the theoretical notions of development, culture and territory, and its link to the concept of territorial identity; (b) to analyze whether and how the production of crafts has changed in the territories where in conversion strategies, and subsequent hybridization processes, compose construction processes and identity projection; (c) to reflect on the potential and limits the craft have to be triggered as diacritical mark in the name of development of the territories where narratives of identity construction and projection are in course. The methodological approach consisted of collection and systematization of secondary data followed by observation and semi-structured interviews with qualified informants. In Costa Doce, a popular tourist territory, the Artesanato no Mar de Dentro Project, coordinated by SEBRAE, has been linking territorial aspects and crafts. From the interviews, it was noticed that the Project activities has contributed to strengthening the sense of belonging of the artisans, who claimed to be proud to contribute to the consolidation and projection of the identity of the territory to which they belong. In the second case study, conducted in Quarta Colônia, the CONDESUS (Consórcio de Desenvolvimento Sustentável da Quarta Colônia) has been promoting, since the beginning of the 1990s, actions in order to assert a territorial identity as a support for its development. The observations and interviews conducted within the Quarta Colônia allowed to state that, despite attempts to promote the identity aspects of the territory promoted by CONDESUS, the symbolic references made in the artifacts, if any, are predominantly specific of the artisan s location, with little reference to the larger territory. At last, it is clear that in the globalized contemporary world, the craft has greater chances to survive when it becomes identity expression, contributing to the construction and projection of the territories, as long as mobilized in conversion strategies for this purpose.